Optimizing the pharmacokinetics of an 211At-labeled RGD peptide with an albumin-binding moiety via the administration of an albumin-binding inhibitor. - Echigo, Hiroaki; Munekane, Masayuki; Fuchigami, Takeshi; Washiyama, Kohshin; Mishiro, Kenji; Wakabayashi, Hiroshi; Takahashi, Kazuhiro; Kinuya, Seigo; Ogawa, Kazuma (European Journal of Nuclear Medicine & Molecular Imaging, 2024)
Purpose: A probe for targeted alpha therapy (TAT) using the RGD peptide (Ga-DOTA-K([211At]APBA)-c(RGDfK) ([211At]1)) with albumin-binding moiety (ABM) was recently developed. [211At]1 highly accumulated in tumors and significantly inhibited tumor growth in U-87 MG tumor-bearing mice. However, high [211At]1 retention in blood may cause critical adverse events, such as hematotoxicity. Therefore, we attempted to accelerate the blood clearance of [211At]1 by competitively inhibiting the binding of [211At]1 to albumin to modulate the pharmacokinetics of the former. Methods: To evaluate the effects of albumin-binding inhibitors in normal mice, sodium 4-(4-iodophenyl)butanoate at 2, 5, or 10 molar equivalents of blood albumin was administered at 1-h postinjection of [211At]1. The biodistribution of [211At]1, SPECT/CT imaging of [67Ga]Ga-DOTA-K(IPBA)-c(RGDfK) ([67Ga]2), and the therapeutic effects of [211At]1 were compared with or without IPBA administration in U-87 MG tumor-bearing mice. Results: Blood radioactivity of [211At]1 was decreased in a dose-dependent manner with IPBA in normal mice. In U-87 MG tumor-bearing mice, the blood radioactivity and accumulation in nontarget tissues of [211At]1 were decreased by IPBA. Meanwhile, tumor [211At]1 accumulation was not changed at 3-h postinjection of IPBA. In SPECT/CT imaging of [67Ga]2, IPBA administration dramatically decreased radioactivity in nontarget tissues, and only tumor tissue was visualized. In therapeutic experiments, [211At]1 with IPBA injected-group significantly inhibited tumor growth compared to the control group. Conclusion: IPBA administration (as an albumin-binding inhibitor) could modulate the pharmacokinetics and enhance the therapeutic effects of [211At]1.